Case Report: A novel approach to prevent chronic histiocytic intervillositis and recurrent pregnancy loss by targeting maternal alloimmunity - Gavillet, Mathilde; Gengler, Carole; Legardeur, Helene; Gannagé, Monique; Puder, Jardena; Beauport, Lydie; Panchaud, Alice; Rotman, Samuel; Comte, Denis; Baud, David; Golshayan, Dela (Frontiers in Immunology, 2025)
Recurrent miscarriage is a distressing condition with limited therapeutic options. Chronic histiocytic intervillositis of unknown etiology (CIUE) is a rare inflammatory placental disorder characterized by maternal immune cell infiltration of the intervillous space, fibrin deposition, and ischemic tissue damage, leading to pregnancy loss. The condition likely reflects an immune response against paternal alloantigens, with histopathological features resembling antibody-mediated rejection in solid organ transplantation. We investigated two women with recurrent CIUE-related pregnancy losses. Detailed immunological profiling included anti-human leukocyte antigen (HLA) antibody characterization, compatibility testing, and histopathological examination of previous placentas, as well as screening for other causes of recurrent pregnancy losses. Based on evidence of antibody-mediated alloimmune injury, we implemented a targeted immunosuppressive regimen derived from transplantation medicine, combining intravenous immunoglobulins (IVIG), tacrolimus, corticosteroids, and hydroxychloroquine, with close pregnancy monitoring. The first patient, after six consecutive CIUE-related pregnancy losses, underwent preconception desensitization and continued treatment throughout pregnancy. Early signs of placental dysfunction prompted therapy intensification, leading to delivery of a viable infant at 33 + 2 weeks. Placental histology showed only minor residual CIUE lesions. The second patient, with two pregnancy losses and a fetal demise from CIUE, began treatment at 6 weeks’ gestation and delivered a healthy infant at 36 weeks. In both cases, therapy was generally well tolerated, with gestational diabetes as the main complication, and no major maternal or neonatal adverse events. These cases support the concept that CIUE represents a breakdown of maternal immune tolerance toward paternal antigens, mediated by fetal-specific anti-HLA antibodies—akin to solid organ graft rejection. An immunosuppressive protocol adapted from transplantation medicine achieved two successful live births after multiple CIUE-related pregnancy losses. Targeting antibody-mediated alloimmunity may represent a promising therapeutic strategy for selected patients with recurrent miscarriages due to CIUE. Further studies are warranted to define optimal regimens and identify predictors of response.